2013
DOI: 10.1007/s00439-013-1273-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of complement genes Ficolin-2, Mannose-binding lectin and Complement factor H are associated with leprosy in Han Chinese from Southwest China

Abstract: The complement system plays multiple roles in host defense against infection and is supposed to confer genetic susceptibility to leprosy. We aimed to examine whether genetic variants of the Ficolin-2 (FCN2), Mannose-binding lectin (MBL2) and Complement factor H (CFH) genes, which are involved in activation and regulation of the complement system, are associated with leprosy in Han Chinese from Southwest China. 527 leprosy patients and 583 matched controls were recruited from Yunnan Province, China, and were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…In HapMap database, the investigated variant -78C/T was widely distributed across all ethnicities and was observed to be in high LD with another variant +4P/Q in the 5' UTR region of exon 1 especially in Han Chinese population. However, no significant associations with leprosy was reported in Han Chinese population [39]. Also in this study, the investigated variants +4P/Q and -78C/T were in strong LD.…”
Section: Accepted Manuscriptmentioning
confidence: 68%
See 1 more Smart Citation
“…In HapMap database, the investigated variant -78C/T was widely distributed across all ethnicities and was observed to be in high LD with another variant +4P/Q in the 5' UTR region of exon 1 especially in Han Chinese population. However, no significant associations with leprosy was reported in Han Chinese population [39]. Also in this study, the investigated variants +4P/Q and -78C/T were in strong LD.…”
Section: Accepted Manuscriptmentioning
confidence: 68%
“…The contribution of this studied MBL2 -78C/T with other diseases is limited. This particular MBL2 -78C/T variant has been reported in Han Chinese and Gabonese populations [39,40]. In HapMap database, the investigated variant -78C/T was widely distributed across all ethnicities and was observed to be in high LD with another variant +4P/Q in the 5' UTR region of exon 1 especially in Han Chinese population.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…The promoter 1 regulates most part of MBL2 transcription, therefore, the polymorphisms in promoter 1 would significantly affect the serum level of MBL2, and among 2 variants identified, it is suggested that −221 Y/X play a more important role. For example, −221 Y/X has been linked with chronic infection in some clinical studies, in addition, a genome wide association study reported the association between −221 Y/X polymorphism and the susceptibility of leprosy among Chinese population9. Our analysis observed the positive correlation between both −550 and −221 polymorphisms and the risk of HCC, the adjusted ORs were 1.61 (95%CI = 1.00–2.57) and 5.67 (95%CI = 1.82–17.67), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the association of FCN2 functional polymorphisms and/or ficolin-2 serum levels with different infectious diseases, including respiratory infections [Atkinson et al, 2004;Ruskamp et al, 2009], pneumonia [Chalmers et al, 2014], invasive pneumococcal disease [Chapman et al, 2007], pulmonary tuberculosis [Luo et al, 2013;Xu et al, 2015], leprosy [de MessiasReason et al, 2009;Zhang et al, 2013], hepatitis B [Hoang et al, 2011;Chen et al, 2015], leishmaniasis [Assaf et al, 2012;Mishra et al, 2015], schistosomiasis [Ouf et al, 2012] or autoimmune diseases with bacterial involvement, such as rheumatic fever and chronic rheumatic heart disease .…”
Section: Discussionmentioning
confidence: 99%